Involvement of Cytokines in the Pathogenesis of Hypersensitivity Pneumonitis: Evaluation of Immunotherapeutic Measures in a Mouse Model - Michel Denis; Marie Bédard; Jacques Gagnon; Yvon Cormier; Michel Laviolette (Canadian Journal of Infectious Diseases)
C57BL/6 inbred strain mice were instilled intranasally with 150 μg/day of the actinomycete Faeni rectivirgula three days a week as a model of farmer's lung disease. Instilled mice developed a strong alveolitis manifested by a large increase in the number of cells in the bronchoalveolar lavage (BAL) (4.1 x 104 cells in saline controls versus 5.28x 105 cells in F rectivirgula-instilled mice). This influx was associated with a substantial release of pro-inflanm1atory cytokine in the BAL; 170 U/mL of interleukin (IL)-1 in instilled mice whereas saline instilled mice had undetectable levels of cytokines in the BAL. In addition, pulmonary fibrosis was evident in challenged mice at three weeks (twofold increase in lung hydroxyproline levels). Infusion of a rabbit antimouse tumour necrosis factor-alpha was associated with an almost complete abrogation of all markers of the disease. Also, administration of cyclosporine A (50 mg/kg/day) partially prevented the alveolitis (P<0.01) and totally prevented cytokine release and lung fibrosis in challenged mice. These findings underscore the tmmunological basis of hypersensitivity pneumonitis, and suggest that antagonism of inflammatory cytokines may hold promise in the treatment of this pathology.